The family of Krikents: from Lithuania — to the banks of the Dnieper - M.P. Chaban; Z.I. Shevtsova; V.V. Gaponov (Gastroenterologìa, 2025)
The article presents the difficult life path of the representatives of the Krikent family of German origin. The head of the family, Karl Krikent, worked at a metallurgical plant in Kamianske, in the Katerynoslav-Dnipropetrovsk region. The family had four sons: Oscar, Rudolf, Alfred, and Edmund. The three older brothers devoted themselves to the medical profession, working selflessly in various medical institutions. Only the youngest, Edmund, chose the field of engineering. A separate story is presented about each of them. Special attention is paid to their descendants, in particular, Maryna Tykhomyrova (granddaughter of Oscar Krikent) who shared her local history research and family memories.